Use of Socio-Scientific Issues in Chemistry Learning - Vegha Dwi Arthamena; Mizzan Ayubi; Sri Atun; Suyanta Suyanta (Postgraduate, University of Mataram, 2024)
Socio-Scientific Issuesis a learning approach that involves social conflict that is closely related to science that has developed in society so that it requires scientific thinking in the presentation of science. The purpose of this research is to find out how effective the SSI approach in teaching chemistry in the high school environment. The method used search using Scopus to get 18 articles to be reviewed. The information is arranged in the following order: type of research, purpose of using the SSI approach, data collection, chemical materials used and field of use of the SSI approach. It is hoped that this discussion can provide guidance for education using the SSI approach in the classroom learning process. The result obtained from the literature review are that SSI can be used in chemistry learning with any material so that it attract the attention of students.